npj Digital Surgery - SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Digital Surgery focuses on the clinical application of artificial intelligence, robotics, and digital health tools. Key topics include deep neural network, machine learning, computer vision, human-AI collaboration, quantum computing, real-time guidance using augmented reality and virtual reality, and kinematics. The journal also highlights innovations in operative anatomy recognition, surgical planning, telepresence, digital surgical care, remote and space surgery. Emphasizing data-driven care, it addresses predictive analytics, outcome optimization, and the ethical, legal, and security challenges of adopting digital technologies in modern surgery. The journal covers a broad range of topics including but not limited to: 1. 1. Artificial Intelligence & Machine Learning in Surgery AI-driven surgical decision-making and risk prediction. Deep learning for surgical planning and real-time assistance. Natural language processing for surgical reporting and analytics. Quantum computing 2. Robotic-Assisted and Autonomous Surgery Development and evaluation of robotic surgical systems. Autonomous technology to enhance surgical procedures and task automation. Human-robot collaboration in complex surgeries. 3. Virtual Digital Surgery Surgical simulation and virtual reality training platforms. Augmented reality for real-time surgical navigation. Digital twins for personalized surgical planning. 4. Remote and Telesurgery Remote surgical interventions. Telepresence enabled surgical collaborations. Access to expert surgical care in resource-limited settings. Space Surgery Digital Peri-operative Surgical Care 5. Data-Driven Surgical Science Big data analytics for surgical outcomes and process improvement. Predictive modeling and decision-support tools. Kinematics analyzing motion patterns and movements during surgery to improve technique and outcomes. 6. Computer Vision & Surgical Imaging Video segmentation for procedure tracking and evaluation. Image-guided surgery and real-time diagnostics. Optics, Imaging, and software technologies to enhance and digitize surgery. 7. New inventions in Digital Surgery Sensors to digitize surgery Multimedia technology in operating rooms. 8. Ethics, Policy & Implementation Cybersecurity, Legal, ethical, and regulatory considerations in digital surgery. The adoption of digital surgery technologies in clinical practice. Equity and access in technology-driven surgical care.
Keywords: Surgery; Endoscopic surgery; Robotics; Biomedical engineering; Surgery; Minimally Invasive Surgery; Robotics; Medical and Health Technologies